2005
DOI: 10.1124/jpet.105.089409
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive Effect of Subcutaneously Injected Interleukin-12 Is Mediated by Endothelin (ET) Acting on ETBReceptors in Rats

Abstract: Interleukin-12 (IL-12) is an inflammatory Th1-driving cytokine that has been clinically used as immune therapy and vaccine adjuvant. Recently, it was reported that patients receiving IL-12 presented hyperalgesia. In the present study, we investigated the mechanical hyperalgesic effect of IL-12 in rats using two tests: 1) paw constant pressure and 2) electronic pressuremeter. In both tests, intraplantar administration of IL-12 (3-30 ng paw Ϫ1 ) caused a dose-and time-dependent mechanical hyperalgesia, which pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 35 publications
(70 reference statements)
3
31
0
Order By: Relevance
“…*, significant difference from baseline (P Ͻ 0.001); #, significant differences from control mice (P Ͻ 0.001). 1998a), injected subcutaneously into the plantar surface of the hind paw, (Baamonde et al 2004;Balonov et al 2006;Gokin et al 2001;Houck et al 2004;Menendez et al 2003b;Piovezan et al 1998Piovezan et al , 2004Verri et al 2004Verri et al , 2005 or skin of the back (Mujenda et al 2007), and injected into tumor-bearing tissues Schmidt et al 2007;Wacnik et al 2001). In contrast, the newer ET A receptor-selective antagonists have been administered systemically (Chichorro et al 2006a;Klass et al 2005;Matwyshyn et al 2006;Piovezan et al 2000;Trentin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…*, significant difference from baseline (P Ͻ 0.001); #, significant differences from control mice (P Ͻ 0.001). 1998a), injected subcutaneously into the plantar surface of the hind paw, (Baamonde et al 2004;Balonov et al 2006;Gokin et al 2001;Houck et al 2004;Menendez et al 2003b;Piovezan et al 1998Piovezan et al , 2004Verri et al 2004Verri et al , 2005 or skin of the back (Mujenda et al 2007), and injected into tumor-bearing tissues Schmidt et al 2007;Wacnik et al 2001). In contrast, the newer ET A receptor-selective antagonists have been administered systemically (Chichorro et al 2006a;Klass et al 2005;Matwyshyn et al 2006;Piovezan et al 2000;Trentin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Injection of ET-1 into the knee or hind paw evokes nocifensive behaviors in animals (Baamonde et al 2004;Balonov et al 2006;De-Melo et al 1998a;Ferreira et al 1989;McKelvy et al 2007;Piovezan et al 1998Piovezan et al , 2004Verri et al 2004Verri et al , 2005. For example, injection of ET-1 into the plantar surface of the hind paw evoked dose-dependent hind paw licking (Gokin et al 2001;Menendez et al 2003b;Piovezan et al 2000), and application of ET-1 directly to the sciatic nerve evoked robust hind paw flinching (Davar et al 1998;Fareed et al 2000).…”
Section: Et-1-evoked Nocifensive Behaviors and Hyperalgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that sST2 is a potent inhibitor of collagen-induced arthritis in mice (11), suggesting that the IL-33-ST2 signaling pathway is a key mediator of rheumatoid arthritis (RA). Arthritic lesions are accompanied by movement limitation secondary to articular hyperalgesia, and there is consistent evidence that cytokines induce hypernociception (hyperalgesia and/or allodynia in experimental animals) (12)(13)(14)(15). Therefore, we have investigated the role of IL-33 in immune inflammatory hypernociception in mice.…”
mentioning
confidence: 99%
“…In this sense, drugs that activate such endogenous opioid mechanisms could represent useful therapeutic approaches (Carvalho et al, 2011;Cunha et al, 2010a;Verri et al, 2006b). Evidence suggests a relationship between opioids and cytokines since opioids inhibit cytokine-induced mechanical hyperalgesia, cytokine production and the consequent recruitment of neutrophils (Clark et al, 2007;Martin et al, 2010;Verri et al, 2004Verri et al, , 2005Verri et al, , 2008bWang et al, 2005). This is an important mechanism since hyperalgesic cytokines such as tumor necrosis factor a (TNFa) and interleukin (IL)-1b are crucial mediators in pain (Cunha et al, 2005(Cunha et al, , 2010b.…”
Section: Introductionmentioning
confidence: 99%